The Impact of Oxytocin on Food Intake and Emotion Recognition in Patients with Eating Disorders: A Double Blind Single Dose Within-Subject Cross-Over Design. - Youl-Ri Kim; Jin-Sup Eom; Jae-Won Yang; Jiwon Kang; Janet Treasure (PLoS ONE)
Background and aim Social difficulties and problems related to eating behaviour are common features of both anorexia nervosa (AN) and bulimia nervosa (BN). The aim of this study was to examine the impact of intranasal oxytocin on consummatory behaviour and emotional recognition in patients with AN and BN in comparison to healthy controls. Materials A total of 102 women, including 35 patients with anorexia nervosa (AN), 34 patients with bulimia nervosa (BN), and 33 healthy university students of comparable age and intelligence, participated in a double-blind, single dose placebo-controlled cross-over study. A single dose of intranasal administration of oxytocin (40 IU) (or a placebo) was followed by an emotional recognition task and an apple juice drink. Food intake was then recorded for 24 hours post-test. Results Oxytocin produced no significant change in appetite in the acute or 24 hours free living settings in healthy controls, whereas there was a decrease in calorie consumption over 24 hours in patients with BN. Oxytocin produced a small increase in emotion recognition sensitivity in healthy controls and in patients with BN, In patients with AN, oxytocin had no effect on emotion recognition sensitivity or on consummatory behaviour. Conclusions The impact of oxytocin on appetite and social cognition varied between people with AN and BN. A single dose of intranasal oxytocin decreased caloric intake over 24 hours in people with BN. People with BN showed enhanced emotional sensitivity under oxytocin condition similar to healthy controls. Those effects of oxytocin were not found in patients with AN. Trial registration ClinicalTrials.gov KCT00000716.